A novel to control defects of P-N semiconductor device by SRFE process - N. Sangwaranatee; Itsara Srithanachai; Surasak Niemcharoen (IOP Conference Series Materials Science and Engineering, 2021)
Abstract This paper present the results from soft radiation flash exposure (SRFE) process. In principle of semiconductor device always has defect in structure from fabrication process and impact from usage environment. Although, device have control process but still has unexpected defects. Then, I would like to share results of SRFE process to control defects in P-N semiconductor device by exposed on device for few second with optimize radiation energy. The defects has disappear after passed SRFE process. The optimize of exposure energy and time will cure or remove defect in devices structure.
Keywords: Semiconductor materials and devices; Radiation Effects in Electronics; Silicon and Solar Cell Technologies